Promoción de la igualdad de oportunidades y mejoramiento del acceso a los servicios sociales. Notas para una estrategia de acción desde el Estado peruano - Cortázar V., Juan (1997)
This article proposes a strategy of government action to promote an equal access to basic social services and lo social insertion opportunities. In the case of social services, it proposes the need to point out the responsibility of the government in relation to the financing and provision of such services. Although the poverty of the country implies that the government should finance directly the greater part of social services, this does not mean that the provision should be exclusively in charge of government institutions. In the case of opportunities of social insertion, it is proposed that the government should invest in the development of human capital and the capabilities of organization of the poor. Special significance is given to the development of social and productive skills since they allow for a better use of the opportunities in question. Finally, this article presents considerations relating not only lo the institutional frame that can make possible the development of the proposed strategy but also the need to convince the taxpayer of the legal standing of public expenditure designed to improve social services and programs of social insertion.